Hepatitis C virus cure before hepatocellular carcinoma diagnosis is associated with improved survival. Issue 5 (2nd February 2021) - Lockart, Ian; Hajarizadeh, Behzad; Alavi, Maryam; Davison, Scott; Prakoso, Emilia; Levy, Miriam T.; George, Jacob; Dore, Gregory J.; Danta, Mark
Abstract: The impact of hepatitis C virus (HCV) cure on survival in patients with HCV‐related hepatocellular carcinoma (HCC) has been examined, although many studies have been subject to survivor treatment selection bias. We assessed the impact of HCV cure before HCC diagnosis on overall survival. Patients with HCV‐related HCC at three referral hospitals in Australia were included retrospectively (January 2008 to December 2019). The risk of death following HCC diagnosis among patients who achieved HCV cure before HCC diagnosis was compared to patients who were viraemic at diagnosis. Among 422 patients with HCV‐related HCC, 101 (24%) achieved HCV cure before HCC diagnosis, 37 with interferon (IFN) and 64 with direct‐acting antiviral (DAA) therapy. Patients with HCV cure were more likely to have no cirrhosis or Child‐Pugh A liver disease (83% vs. 66%, p  = .002), surveillance detection (71% vs. 48%, p  < .001), HCC stage O or A (64% vs. 45%, p  < .001) and receive curative initial HCC management (51% vs. 28%, p  < .001), compared with patients who were viraemic at diagnosis. The 5‐year overall survival was 51% in the HCV cure group and 22% in the viraemic group. In adjusted analysis, risk of death was lower in patients with HCV cure before HCC diagnosis compared with patients who were viraemic at diagnosis (adjusted hazard ratio: 0.63; 95% CI: 0.44–0.91; p  = .013). Patients with HCV‐related HCC who have achieved HCV cure before HCC diagnosis have improved overall survival compared with patients who were viraemic at diagnosis.